The Entanglements of English in Contemporary Greenland - Jacobsen, Ushma (Études Inuit Studies, 2023)
Greenland’s international presence intertwines with its emerging status as an autonomous Arctic nation and with reconfigurations of the postcolonial identities of its people. In this article, I explore the positions and practices of English in Greenland in relation to two conditions of ambivalence: the ambivalence of English as both imperialistic and empowering, and the ambivalence that textures postcolonial Kalaallit-Danish relations. I consider how exploring the arguments, desires, and contestations of English, gathered through diverse empirical fragments, draws attention to the entanglements of multidirectional aspirations, diverse communities, new technologies, and altered geographies. The connections to English emerge in the everyday communicative practices of Greenland’s people and in the demands of organizations and industries. These connections are just as formidable as those stemming from political rhetoric and policies. I propose that the significance of English is in the making and conclude by outlining three areas of further collaborative research to follow this development for Kalaallisut, for Kalaallit-Danish relations, and for the production of new forms of equalities and inequalities.